Growth (But Not Only) Is Good for the Poor : Some Cross-Country Evidence to Promote Growth and Shared Prosperity in Haiti - Antoine, Kassia; Singh, Raju Jan; Wacker, Konstantin M. (World Bank, Washington, DC, 2017)
Many low-income countries, such as Haiti, have high ambitions and socioeconomic needs to achieve substantial income growth, especially for the poorest income quintiles. This situation raises the question of policy prioritization, which is often difficult to address, since reliable country-specific micro data are scarce in most low-income countries. Although many studies have investigated the determinants of growth of gross domestic product, less is known about the factors influencing household incomes at the lowest segments of the income distribution. Focusing on the specific case of Haiti, a country with one of the lowest income levels, this paper proposes an approach to handle this challenge: it estimates income drivers for the poorest two income quintiles from cross-country regressions. The results suggest that maintaining macroeconomic stability as well as investing in human and physical capital would not only be associated with faster overall economic growth, but also with even faster income growth for the poorest segments of the population. Thus, there need not be a trade-off between inequality and growth. Economies could foster faster growth while also increasing inclusiveness, ensuring that everyone can live up to their potential.